Introducing the National Library for Health Skin Conditions Specialist Library - Grindlay, Douglas J.C.; Kamel Boulos, Maged N; Williams, Hywel C. (Biomed Central, 2005)
Background: This paper introduces the new National Library for Health Skin Conditions Specialist Library http://www.library.nhs.uk/skin. Description: The aims, scope and audience of the new NLH Skin Conditions Specialist Library, and the composition and functions of its core Project Team, Editorial Team and Stakeholders Group are described. The Library's collection building strategy, resource and information types, editorial policies, quality checklist, taxonomy for content indexing, organisation and navigation, and user interface are all presented in detail. The paper also explores the expected impact and utility of the new Library, as well as some possible future directions for further development. Conclusion: The Skin Conditions Specialist Library is not just another new Web site that dermatologists might want to add to their Internet favourites then forget about it. It is intended to be a practical, "one-stop shop" dermatology information service for everyday practical use, offering high quality, up-to-date resources, and adopting robust evidence-based and knowledge management approaches.